The sui generis right to non-original objects generated by a computer program: novelties of legal regulation - Doroshenko, Oleksandr; Tarasenko, Leonid (Theory and Practice of Intellectual Property, 2023)
The article considers novel legal regulations regarding non-original objects generated by a computer program. It was established that at the level of the law, legal certainty was introduced regarding the legal regime of these objects: the concept and characteristics of a non-original object, generated by a computer program, subjects of property rights, the scope of such rights, their validity period, the possibility of transfer (alienation) were defined) of these rights, as well as an opportunity to properly protect such rights. The signs of a non-original object generated by a computer program are defined: difference from already existing similar objects; creation of an object solely as a result of the operation of a computer program without direct human participation. It has been proven that the independent legal personality of artificial intelligence is highly debatable, and this concept goes far beyond the boundaries of intellectual property law. It is justified that giving artificial intelligence an independent legal personality as of today is a hasty step, therefore the approach reflected in the law deserves attention.It is substantiated that the legal regime of an object that is non-original and that is generated by a computer program is very similar to the legal regime of a work as an object of copyright, which enables the relevant subjects to exercise and protect the rights to these objects. It was established that as a result of the creation of a non-original object generated by a computer program, personal non-property rights do not arise at all, and property rights belong to the owner of the property rights to the computer program that generated such an object. It has been proven that the property rights to a nonoriginal object are in fact identical to the property rights of the author (other subjects of property copyright), the scope of which is determined by Article 12 of the Copyright Law.It is established that when creating a non-original object generated by a computer program, one should observe the property rights to other non-original objects generated by a computer program, which are used in the process of generating a new non-original object; to objects of copyright and/or related rights that were used in the process of generating such non-original object.